The first stone - Jensen, Carsten, 1952- (Amazon Crossing, 2019)
"Dispatched to fight the Taliban as part of the NATO forces, the soldiers of the Third Platoon arrive in a desert hell intent on testing their courage and endurance. Among them are the charismatic platoon leader Schrøder, a former games designer fascinated by the imaginative potential of war; Colonel Steffensen, whose negotiating tactics will have deadly consequences; Sidekick, the LifeLogger whose online “war memorial” will blur into horror; and the hardened but vulnerable Hannah, who must bury her womanhood - or sacrifice her soul. Confronted by a betrayal that no military training could prepare them for, the soldiers must embark on a desperate mission to track down an enemy whose methods are as murderous as they are unfathomable. As the hunters become the hunted, the mission turns into a depraved, hallucinatory voyage into an Afghanistan they never knew existed. With the Third Platoon's most fundamental notions of good and evil called into question, survival becomes their only mission. "--Publisher description.